Ladies in armour : a phenomenological investigation of experiences of highly skilled Finnish female kendo athletes - Dekšnytė, Rita (2013)
Women in sports have historically been marginalised. Feminist studies have revealed a struggle to balance athletic and feminine identities in “conventionally masculine” sports. However, there is a need to explore women's experiences in a variety of sports. Interpretative Phenomenological Analysis was used to explore the experiences of three highly skilled Finnish female athletes of Japanese kendo in order to better understand personal and social meanings of gender and sport. Participants were asked to write a personal story based on a prompt statement “A woman in kendo” and comment on other participant's stories. The data was then interpreted and the following broad themes emerged: personal, socio-cultural, gender and sports framework. The findings reveal that personal motivations to practice kendo are related with the process of personal development and learning skills that can be transferred into other areas of life; perceptions of gender construction and gender differences vary among the participants; kendo sports framework is seen as facilitating non-gendered interactions through promotion of equality and respect; differences between Finnish and Japanese socio-cultural contexts become evident as participants discuss gendered cultural encounters. The findings can be relevant to those committed to creating bias-free sporting environment, assuring equal access and increasing participation in sports.